Regularities of bitumen hydrothermal associations in geological structures of West Donetsk graben - Іщенко, Л. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Accommodations of bitumen-hydrothermal associations in geological structures of the West of Donetsk graben have been studied. It has been stressed that the main tectonic elements of the region are long-lived deep faults. The main role is played by the fault intersection zones of different directions, which are associated with the processes of heat and mass transfer. They appear in the hydrothermal mineralization, new and modern tectonic movements, heightened tension of the thermal field, as well as the ascending discharge of endogenous gases, hydrocarbon fluids and deep water formations. It is established that a characteristic feature of the region is the presence of bitumen-hydrothermal associations’ anticline that presents ore in areas of rocks decompression (mercury and mercury-polymetallic) as well as barren mineralization, and on the other hand- bitumen. According to the author, the main reason for such an existence in the geological space is, above all, general migration routes of mineralizing fluids of different geochemical specialization. An educated guess is that the main geological-structural and geochemical features of the West Donetsk graben were formed in the Laramide phase of the Alpine orogeny, which caused a significant intensification of heat and mass transfer processes, resulting in the formation of hydrothermalites that closely co-exist with a variety of hydrocarbon compounds - from methane gas to solid solutions.